Low-Cost Technology to Improve Aviation Safety and Efficiency : Investment Program Brings Modernized Aviation Information Technology to Pacific Islands - De Serio, Christopher; Giovannitti, Aldo (World Bank, Washington, DC, 2017)
The World Bank’s Pacific Aviation Investment Program (PAIP) is bringing state-of-the-art air traffic management and satellite-based ground communications to airports and small aircraft operators in seven Pacific island countries and territories. These advances, coming online in 2017, will vastly improve the safety and efficiency of South Pacific aviation and further its global integration. The air traffic surveillance equipment, known as ADS-B, surpasses the abilities of radar to locate aircraft en route and does so at one-tenth the cost. ADS-B increases the safety of flying and improves search and rescue operations; it also enables more efficient flight routing, which saves fuel and reduces greenhouse gases. The installation of the surveillance equipment at ground stations in five Pacific island countries, Kiribati, Samoa, Tonga, Tuvalu, and Vanuatu, and in smaller aircraft will significantly broaden the coverage of aviation activity across the region. A new satellite-based ground-to-ground communications network will link those five countries plus Cook Islands and Niue. The network will be resistant to natural disasters, thus improving emergency preparedness and response. More broadly, strengthening aviation-related communications in the Pacific will help integrate the Asia-Pacific region with global developments in air traffic information systems.